تقييم فعالية كل من البوتكس وإعادة تموضع الشفة في تصحيح الابتسامة اللثوية - خليل, عبد الكريم; العساف, أريج; مكية, محمد (Latakia University Journal -Medical Sciences Series, 2018)
This study aims to evaluate the effectiveness of both injection botulinum toxin type A (botox) and surgical lip reposition in the correction of the gummy smile due to hyperactive upper lip according to gingival display, the resulting smile and the patients satisfaction. This is done to determine the less damaging to the tissues and more stable alternative in giving results with statistical importance and esthetically satisfying results. The method consists of 24 patients: 12 received the BTX-A injection and the remaining 12 underwent the surgical procedure (lip reposition). The patient rated their satisfaction according to their gingival display that was defined as the difference between the lower margin of the upper lip and the superior margin of the right incisor and. Patients were followed at 2 weeks, 2 months and 6 months. Post injection and post surgery with changes documented by photographs and both groups answered a questionnaire addressing overall the appearance and asked to rate the improvement of their smile according to a 5-point aesthetic scale. We observe that in the case of surgery, the average of gingival display pre-surgery was (4.250 ±0.846) . After 2 weeks of surgery gingival display had decline to (1.167 ±0. 778) but after 2 months gingival displayhad increased to (1.583 ±0.469). After 6 months gingival display had increased to (3.299 ±0.0752) Preinjection gingival display averaged was (4.292 ±0.531). After 2 weeks of surgery gingival display had decline to (0.458 ±0.0382) but after 2 months gingival displayhad increased to (1.729 ±0.376) . After 6 months gingival display had increased to (3.938 ±0.545) Based on the previous observation, it's obvious that the correction f the gummy smile by BTX-A had given better results at 2 weeks and 2 monthsthan surgery. Howeever, At 6 months, the difference of the average of gingival display between BTX-A injection and lip reposition Surgery is not notable. Even though both methods of treatment have transitory results after 6 months of treatment. BTX-A injection exhibits better results than those of surgery and had given safer and more satisfactory than lip reposition. The Patients rated the effects of BTX-A as highly favorable during the observation if we take into consideration that BTX-A was temporary effect but the surgical procedure ( lip reposition ) is 80% recurrent surgery due to the lip reverted back to its original position with almost complete relapse after 6 months later and containing all the dangers affiliated with the surgical procedures. هدفت هذه الدراسة إلى تقييم فعالية كل من حقن ذيفان البوتولينيوم من النوع A (بوتوكس) Botox كمادة حقن شالة للعضلات وإعادة تموضع الشفة Lip Reposition كعمل جراحي جمالي في تصحيح الابتسامة اللثوية الناتجة عن فرط نشاط الشفه العلوية HYPERACTIVE UPPER LIP من حيث كمية التغطية اللثوية وعرض الابتسامة الناتجة ورضا المريض وتحديد البديل الثابت والأقل ضررا للنسج حيث يقدم نتائج ذات أهمية إحصائية ومرضية من الناحية الجمالية والوظيفية للمريض . تتألف عينة البحث من 24 حالة لمرضى ذات ابتسامة لثوية ناتجة عن فرط نشاط الشفه العلوية ، حيث تم حقن ذيفان البوتولينيوم من النوع A (بوتوكس) على 12 مرضى و تم إجراء عملية إعادة تموضع الشفة على 12 مرضى ثم تضمنت المراقبة السريرية أخذ صورة بالوضعية الأمامية وصورة بالوضعية الجانبية من الجهتين قبل المعالجة وبعد أسبوعين و شهرين و 6 أشهر . أظهرت نتائج هذه الدراسة أنه بالنسبة للجراحة أن عرض الانكشاف اللثوي كان قبل الجراحة (4.250±0.846 ملم)و قد تناقص بعد أسبوعين للمقدار 1.167±0.0778 وبعد شهرين من الجراحة نجد أن الانكشاف اللثوي قد أزداد إلى ا 1.583 ±0.469 ملم وبعد 6 أشهر من الجراحة اصبح مقدار الانكشاف اللثوي 3.229±0.752 بيمنا بالنسبة للحقن نجد أن الانكشاف اللثوي كان قبل الحقن كان متوسط الانكشاف اللثوي فوق الثنية قبل الحقن(4.292±0.531 ملم) بعد أسبوعين قد تناقص للمقدار 0.458±.0.0382 وبعد شهرين من الحقن نحد أن الانكشاف اللثوي قد أزداد إلى 1.729 ±0.376 ملم وبعد 6 أشهر من الحقن اصبح مقدار الانكشاف اللثوي 3.938±0.545 ومنه نجد أن المعالجة بالبوتكس قد أعطت نتائج افضل خلال أسبوعين وخلال شهرين اما بعد 6 اشهر نجد ان الفرق بسيط بين الطريقتين وبذلك يكون الحقن اكثر امان وافضل خيار كون الفرق في الانكشاف اللثوي بين الجراحة والبوتكس بسيط مع بقاء الرضا عند المرضى عند المعالجة بحقن ذيفان البوتولينيوم من النوع A (بوتكس) أعلى من المعالجة بالجراحة. إن المعالجة بواسطة حقن ذيفان البوتولينيوم من النوع A (بوتوكس) تعطي نتائج افضل من المعالجة بواسطة الجراحة في تصحيح الابتسامة اللثوية الناتجة عن فرط نشاط الشفه العلوية اذا اخذنا بعين الاعتبار أن العمل الجراحي ( إعادة تموضع الشفة ) ناكس بنسبة 80 % و كافة المخاطر المحتملة التي قد تنتج عن العمل الجراحي.